(untitled) (Research, Society and Development, 2023)
This work aims to analyze in scientific articles, national and international books, the possible intercurrences during and after procedures involving Polydioxanone (PDO) threads. It is a research with bibliographical search in Scielo, Medline and autographed books databases. Studies point out that the use of Polydioxanone suture thread presents few intercurrences and that, if they occur, most of the time they are easily resolved, although serious intercurrences rarely occur. With this research, it was concluded that the Polydioxanone threads, when well indicated and applied in the correct plane of the face, lend themselves to a perfect lifting, without incisions or seclusions of the patient. There is a quick recovery of the patient after the procedure and good results with the benefit of neocollagenesis.